Pengaruh Penerapan Sistem E-Filing, Sosialisasi Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada KPP Pratama Maumere - Kristina Febiyanti Nona Cindri; Wilhelmina Mitan; Emilianus Eo Kutu Go’o (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to examine the effect of implementing the e-filing system, outreach and tax sanctions on individual taxpayer compliance. The population in this study is an individual taxpayer at the Pratama Maumere Tax Service Office in 2022 with a total of 113,653 people. This type of research is a quantitative research by distributing questionnaires. The sampling technique used in this study was accidental sampling, namely a sampling technique from members of the population based on coincidence, that is, anyone who coincidentally meets the researcher and the person met by chance is suitable and in accordance with the criteria can be used as a data source. The number of samples in this study were 100 individual taxpayer respondents. The analytical method used is multiple linear regression analysis with the SSPS program. The results of the study show that the application of e-filing has a significant effect on individual taxpayer compliance, tax socialization has a significant effect on individual taxpayer compliance, and tax sanctions have a significant effect on individual taxpayer compliance, and the application of e-filing, socialization and tax sanctions are the same - equally affect the compliance of individual taxpayers.